Factors affecting length of stay in Children Hospital in Southern Iran - Baniasadi, Tayebeh (BMC Health Serv Res, 2019)
BACKGROUND: One of the effective indicators for determining the efficiency and optimal use of hospital resources is the length of stay (LOS). This study aimed to determine the patients’ length of stay and the factors affecting the LOS in the Children’s hospital. METHOD: A cross-sectional study was performed on Children Hospital medical record database including 350 records (April 2015 to Dec 2015). Records were selected by stratified random sampling with proportional allocation. Then the predetermined demographic and hospital variables were extracted through the study of patients’ medical records. All statistical analysis were performed using SPSS software. RESULTS: The overall median of the LOS in the studied hospital was 3 days (IQR =3). The results showed that in this hospital the LOS has a significant relationship with the variables of time of admission, the place of residence, type of admission, and the degree of attending physician. Also, with the increasing number of visits, ultrasonography, counseling and laboratory test, LOS was increased. CONCLUSION: Improving processes related to diagnostic procedures, providing adequate staffing for specialized services in all hours of the day, preventing unnecessary and non-emergency admissions in the evening and night, will be effective in optimizing patient LOS.